The impact of aging and thickness on flexural strength of various zirconia ceramics - Oyku Silmeoglu Yagli; Esra Talay Cevlik; Duygu Kurklu Arpacay (BMC, 2024)
Abstract Background Effects of the aging process on the flexural strength of Y-TZP and different Y-PSZ ceramics of different thicknesses were investigated. Methods 300 disc-shaped samples (12 mm diameter, 0.8 and 1.5 mm thicknesses) were made from 5 different zirconia materials 3Y-TZP LA, 4Y-PSZ, 5Y-PSZ, 3 + 5Y-PSZ and 4 + 5Y-PSZ. Experimental groups were artificially aged in an autoclave at 134 °C, 2 bar pressure for 1 and 5 h; control groups were not subjected to any treatment. Microstructural analysis was conducted using Scanning Electron Microscopy, and X-Ray Diffraction analysis determined the crystalline phase content. The impact of aging on flexural strength was investigated with the use of the biaxial flexural strength test. Data were analyzed using three-way ANOVA tests with a significance level of p < 0.05, applying Bonferroni correction for multiple comparisons. Results Statistically significant differences in flexural strength were observed among the materials and the material thicknesses (p < 0.05), while there were no significant differences among the aging times (p > 0.05). The highest mean flexural strength values were recorded in the case of the 3 Y-TZP-1.5 mm-5 h group (744.1 ± 61.2 MPa), which was attributed to phase-transformation toughening. The lowest values were observed in the case of the 5 Y-PSZ-1.5 mm-5 h (338.3 ± 34.8 MPa) group. Conclusions Both material type and thickness significantly affect the flexural strength of zirconia ceramics, whereas aging time does not; thus, material selection and thickness are crucial considerations for clinicians.